PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPA KELAS V SDN 1 KARANG MARITIM - Fadilah, Nawaf; Sugiyanto, Sugiyanto; Rahmawati, Divya Zuhra (AHSANTA JURNAL PENDIDIKAN, 2024)
This research aims to analyze the influence of the project based learning model on the learning outcomes of class V students in science subjects at SDN 1 Karang Maritim Bandar Lampung. This research is quantitative research with a quasi-experimental type using a one group pretest-posttest form. The population in this study were class V students at SDN 1 Karang Maritim Bandar Lampung. Determination of the sample using the Non-random Sampling technique using the Purposive Sampling sample type. Data collection techniques and data collection instruments use test and documentation techniques. The data analysis technique used is the paired sample t-test. The research results are shown by the results of the t-test (paired sample t-test) for the same sample with different treatments (pretest-posttest) of 9.788 with a Sig. level (2-tailed) 0.000<0.05. This shows that there is an influence of the project based learning model on the learning outcomes of class V students in science subjects.